Pengaruh Tingkat Pendapatan Dan Pengetahuan Zakat Profesi Terhadap Minat Berzakat Di Kalangan Milenial - Rosyidah, Norma; Nausan, Aira Vema Mutiara; Faujiah, Ani (CV. Kalimasada Group, 2023)
Professional zakat is a common thing to hear among Muslims, one of the obligations that must be carried out in accordance with the guidance of syariát. In the current conditions where millennials are a generation that has a fairly high population and has unique characteristics based on region and socio-economic conditions. The millennial generation is also a generation that is familiar with the use of communication tools, media, and digital technology. In this case, it is very possible for the millennial generation to be able to have a job that has a promising income level and has extensive knowledge about important things or issues, the only thing about the obligation of professional zakat. The results showed that the variable income level had a significant effect in the interest in the difference among millennials. The variable knowledge of professional zakat has a significant effect on the interest in charity among millennials. Variables in the level of income and knowledge of professional zakat simultaneously have a significant effect on the interest in charity among millennials.